Implementation of Contextual Strategies in Learning Malay-Language Classical Islamic Texts at STIT Darul Ulum Kotabaru - Solikin, Hilal (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to analyze the implementation of Contextual Teaching and Learning (CTL) strategies in teaching Malay-language Islamic texts at STIT Darul Ulum Kotabaru. The research is motivated by the declining interest of students in studying classical texts and their difficulties in understanding classical Malay manuscripts containing Arabic terminology. This study employs a qualitative approach using a case study design. Data were collected through classroom observations, in-depth interviews, and document analysis. The findings indicate that lecturers implemented various strategies, including collaborative translation, problem-based learning, the use of digital media, and collaboration with the community. The application of these strategies positively influenced students’ learning motivation, conceptual understanding, and analytical skills. Nevertheless, several challenges were identified, such as limited digital learning resources, restricted instructional time, and the diverse educational backgrounds of students. The study recommends strengthening lecturers’ competencies in developing contextual teaching materials and improving supporting facilities to enhance the effectiveness of the learning process.